2004
DOI: 10.1175/jtech-1680.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Height Predictions from the Global Navy Coastal Ocean Model during 1998–2001*

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to the Department of Defense, Executive Services and Communications Directora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…The second velocity field that we used comes from the Navy Coastal Ocean Model (NCOM), a high-resolution numerical model (Barron et al, 2004(Barron et al, , 2006. A regional model with 3 km horizontal resolution was nested with open boundaries within the HYCOM global 1/8 • model.…”
Section: Modeling the Spreading Of 137 Csmentioning
confidence: 99%
“…The second velocity field that we used comes from the Navy Coastal Ocean Model (NCOM), a high-resolution numerical model (Barron et al, 2004(Barron et al, , 2006. A regional model with 3 km horizontal resolution was nested with open boundaries within the HYCOM global 1/8 • model.…”
Section: Modeling the Spreading Of 137 Csmentioning
confidence: 99%
“…Initial conditions and daily boundary conditions were taken from a hind-cast of a global model (Barron et al, 2004). The numerical treatment of the boundary conditions includes the Flather radiation condition (Flather and Proctor, 1983) for the surface elevation and depth-averaged normal velocity, Orlanski radiation conditions (Orlanski, 1976) for the tangential velocities and scalar fields, and a relaxation to the temperature and salinity from the global model near the open boundary.…”
Section: Coastal Model and Configurationmentioning
confidence: 99%
“…The 3D implementation of the model typically uses six equally spaced sigma layers in vertical-this number was determined by comparing simulations obtained with 4,6,8,16 layers, which found that 6 layers were sufficient to resolve the pycnocline and that going from 6 to 8+ layers provides negligible differences in simulation results. …”
Section: Acms Model Domains and Forecast Cyclesmentioning
confidence: 99%